2014
DOI: 10.1590/s1982-56762014000400010
|View full text |Cite
|
Sign up to set email alerts
|

Episomal detection of Banana streak OL virus in single and mixed infection with Cucumber mosaic virus in banana 'Nanicão Jangada'

Abstract: Banana streak virus (BSV) and Cucumber mosaic virus (CMV) are commonly found in all banana growing-areas of the world. These viruses cause diseases that lead to yield reduction and constrain plant breeding and distribution of Musa germplasm. Most of the diagnostic methods targeting BSV can generate dubious results because of the considerable genetic and serological diversity among BSV isolates and the presence of integrated BSV sequences in the banana plant. Both viruses are usually detected in single and mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…BSV infections cause typical leaf streak symptoms, which tend to be intermittent in expression. Diseased plants may be stunted, showing pseudostem splitting and necrosis of the leaf cigar, and fruit may be distorted (Gauhl and Pasberg-Gauhl 1995;Lockhart and Jones 1999;Fargette et al 2006;Carnelossi et al 2014). BSV is transmitted by several mealybug species in a non-persistent manner (Kubiriba et al 2001;Meyer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…BSV infections cause typical leaf streak symptoms, which tend to be intermittent in expression. Diseased plants may be stunted, showing pseudostem splitting and necrosis of the leaf cigar, and fruit may be distorted (Gauhl and Pasberg-Gauhl 1995;Lockhart and Jones 1999;Fargette et al 2006;Carnelossi et al 2014). BSV is transmitted by several mealybug species in a non-persistent manner (Kubiriba et al 2001;Meyer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the genera, families, and orders to which EFFs mostly belong within the three clades. As observed, the vast amount of EFF species correspond to eudicots; specifically, plant species of the genera Rubus (161), Prunus (112) and Crataegus (74), constituted the largest family of Rosaceae (575), order Rosales (685) (Figure 1). EFFs belonging to families Ericaceae (135) and Solanaceae (92) were also numerous, in which the genera Vaccinium (56) and Solanum (36) were highly represented, respectively (Figure 1; Supplementary Table S1).…”
Section: Edible Fruits Of the World: Which Of Them Feed The World?mentioning
confidence: 71%
“…On the other hand, Hanssen et al found that PepMV recombinants frequently occur in mixed infections under natural conditions [110], showing that coexistence of viruses is a prerequisite for recombination events. In this matter, banana mild mosaic virus (BanMMV), an unassigned genus within the Betaflexiviridae family, is often detected in mixed infection with CMV, banana streak virus (BSV; Badnavirus, Caulimoviridae), and banana bract mosaic virus (BBrMV; Potyvirus, Potyviridae) [111,112].…”
Section: A Co-evolutionary Arms Race Between Plants and Viruses: Majo...mentioning
confidence: 99%
“…The relatively large genomic variation among BSVs makes it difficult to design RT-LAMP assay capable of detecting all BSV species. Banana plants occasionally are infected by several viruses in the field (Brioso et al 2000;Carnelossi et al 2014). Most multiplex assays developed to detect virus infections in banana are based on PCR (Tan et al 2010;Prema et al 2012).…”
Section: Discussionmentioning
confidence: 99%